2020
DOI: 10.1049/iet-pel.2019.1568
|View full text |Cite
|
Sign up to set email alerts
|

Family of single‐phase isolated high‐frequency transformer integrated improved magnetically coupled Z‐source ac–ac converters

Abstract: This study proposes single-phase improved coupled-inductor (CL) Z-source (ZS) ac-ac converters with integrated high-frequency transformer (HFT) isolation. They can provide wide range of buck-boost voltage with same/reversed phase angle, similar to the existing ZS ac-ac converters. Meanwhile, integrating a HFT with CL in proposed converters benefit in twofold: (i) the CL enhances the voltage gain, which in turn reduces the voltage stresses/ratings of active switches. Moreover, the turns ratio of CL add another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The minimum capacitances of capacitors and inductances of inductors are derived from the optimal current and voltage ripple values. The volume metric of the converter is calculated by (25) and (26) based on the energy stored in the inductor, coupled inductor, and capacitors.…”
Section: Volume Metric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum capacitances of capacitors and inductances of inductors are derived from the optimal current and voltage ripple values. The volume metric of the converter is calculated by (25) and (26) based on the energy stored in the inductor, coupled inductor, and capacitors.…”
Section: Volume Metric Analysismentioning
confidence: 99%
“…An advance switching strategy for single and three‐phase AC‐AC converters has been introduced in Fang et al, 21 Li et al, 22 and Tang et al 23 to solve the commutation problem and eliminate the snubber circuit. The most popular impedance networks in single‐phase AC‐AC converters to operate in‐phase or 180° phase‐shift regarding the input voltage have been introduced 24–26 . Ahmed et al 25 have suggested a family of isolated single‐phase Z‐source AC‐AC converters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, D must be increased to achieve an HV gain; however, it causes HV tensions in network components [10]. Therefore, a variety of topologies for ZS-based DC-DC converters have been proposed using magnetic connection methods (e.g., methods that use transformers) to eliminate this problem, optimize voltage gain, and reduce voltage stress [11]. The current study primarily concentrates on ZS-based DC-DC converters with isolation transformers.…”
Section: Optimization Of Impedance-source Galvanically Isolated Dc-dc Converters With Reduced Number Of Switchesmentioning
confidence: 99%
“…Based on Equations ( 5) and ( 8), the average value of the DC-link voltage between the power switches (S) (i.e., v pn.av ) can be computed as Using Equation (11), the peak output voltage of the Zsource impudence can be expressed as follows:…”
Section: A Operating Principles Of the Proposed Circuitmentioning
confidence: 99%